A method for sintering low silicon, low basicity, ultra-thick vanadium-titanium material layer
Through multiple mixing and multi-layer fabric optimization, the sintering process is solved, the problem of poor sintering effect of super-thick material layers is improved, the TFe content and strength of the sintered ore is met, the blast furnace production needs is met, and low-carbon and environmentally friendly sintering is achieved.
Patent Information
- Application Number
- CN202211600685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The existing sintering methods are poor when sintering the super-thick material layer, and are prone to form phases such as brittle perovskite and titanium garnet, resulting in a high SiO2 content and a high CaO content of the sintered ore. The strength and particle size of the sintered ore are not suitable for blast furnace production.
Multiple mixing treatments are used to make the sintered material uniform, improve the particle size composition of the mixed spheres, sinter the super-thick material layer through multiple layers of fabrics, and preheat the material on each layer to optimize the fabric structure to improve the sintering effect.
The TFe content of the sintered ore is increased, the alkalinity of the sintered ore is increased, the strength and particle size of the sintered ore is met, and the energy consumption of the sintered process is reduced, thus achieving low-carbon and environmentally friendly sintering.
Smart Images

Figure CN115747482B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of blast furnace ironmaking, and in particular relates to a method for sintering a low-silicon, low-basicity, vanadium-titanium ultra-thick material layer. Background Art
[0002] Sintering refers to the process of converting powdered materials into dense bodies. It is a traditional process that people have used to produce ceramics, powder metallurgy, refractory materials, ultra-high temperature materials, etc. Generally speaking, after the powder is formed, the dense body obtained by sintering is a polycrystalline material, and its microstructure is composed of crystals, glass and pores. The sintering process directly affects the grain size, pore size and grain boundary shape and distribution in the microstructure, which in turn affects the performance of the material.
[0003] Sintering is an important link in the steel production process. It is a process of mixing iron ore powder, anthracite powder and lime in a certain ratio. The sintered ore with sufficient strength and particle size can be used as clinker for ironmaking. Using sintered clinker to make iron is of certain significance in improving the utilization coefficient of blast furnace, reducing coke ratio, improving the permeability of blast furnace and ensuring the operation of blast furnace.
[0004] At present, the raw material structure used by steel sintering plants is mainly vanadium titanium concentrate powder. 2 When the content is less than 4.8% and the CaO content is less than about 10.5%, a large amount of brittle perovskite (CaO·TiO 2 ), titanium garnet and other phases. At the same time, due to the significant reduction in the amount of sintering liquid phase, the decrease in the sintering drum index, the increase in the anti-wear index, the increase in the return rate, the decrease in sintering ore output and the sharp increase in fuel and electricity consumption, it is not conducive to the subsequent smelting production.
[0005] In order to increase the TFe content of sintered ore and reduce the basicity of sintered ore, and to meet the production needs of blast furnaces under the current raw material structure conditions, while reducing the energy consumption of the sintering process and achieving low-carbon and environmentally friendly sintering, it is necessary to innovate the ultra-thick layer sintering technology from the process technology to solve the above-mentioned problems. Summary of the invention
[0006] The purpose of the present invention is to provide a method for sintering ultra-thick layers of low-silicon, low-alkalinity, vanadium-titanium materials, which uses multiple mixing treatments to make the composition of the sintering material uniform, improve the particle size composition of the mixed material balls, and enhance the air permeability of the sintering material layer. A multi-layer material distribution method is used to improve the overall sintering effect, thereby solving the problem that the existing sintering methods have poor sintering effects when sintering ultra-thick material layers, and are prone to forming a large amount of brittle perovskite, titanium garnet and other phases during the sintering process.
[0007] To solve the above technical problems, the present invention is achieved through the following technical solutions:
[0008] The present invention is a method for sintering a low-silicon, low-basicity, ultra-thick vanadium-titanium material layer, comprising the following steps:
[0009] S1: crushing and sieving the vanadium-titanium concentrate to obtain vanadium-titanium concentrate powder, crushing and sieving the solvent to obtain solvent powder, crushing and sieving the fuel to obtain fuel powder, and drying the solvent powder and the fuel powder;
[0010] S2: batching based on mass, and uniformly mixing corresponding weight portions of vanadium-titanium concentrate powder, solvent powder, fuel powder and water, and granulating to obtain mixed material pellets;
[0011] S3: Arrange the super thick material layer of ≥880mm through the distributor, the super thick material layer includes the lower mixed material layer, the lower fuel powder layer, the middle mixed material layer, the upper fuel powder layer and the upper mixed material layer, and preheat the materials in each layer when arranging each layer;
[0012] S4: start ignition and sintering;
[0013] S5: After sintering is completed, crushed, screened and cooled, a sintered block product is obtained.
[0014] Furthermore, the particle size of the vanadium-titanium concentrate powder in S1 is controlled to be less than 5 mm, the particle size of the solvent powder is controlled to be less than 3 mm, and the particle size of the fuel powder is controlled to be less than 3 mm; the particle size composition of the mixed material pellets is improved, and the permeability of the sintered material layer is improved.
[0015] Furthermore, after the solvent powder and the fuel powder are dried in S1, the moisture content of the solvent powder is less than 3%, and the moisture content of the fuel powder is less than 10%.
[0016] Furthermore, the mixing in S2 specifically includes the following steps:
[0017] S21: mechanically mix the solvent powder, the fuel powder and 50% by weight of the vanadium-titanium concentrate powder, then add an appropriate amount of water to moisten them, and then mechanically mix them again;
[0018] S22: adding the remaining 25% vanadium titanium concentrate powder to the mixture of S21, and continuing to mix mechanically;
[0019] S23: adding the remaining 25% vanadium titanium concentrate powder to the mixture of S22, and continuing to mix mechanically;
[0020] S24: The mixed material of S23 is processed by a granulating screen to obtain qualified mixed material pellets.
[0021] Furthermore, in S24, the mixed material pellets are dried by hot air flow to make their water content less than 15%.
[0022] Furthermore, the arrangement of the super thick material layer in S3 specifically includes the following steps:
[0023] S31: first arrange the lower mixed material layer, spread the mixed material balls flat on the sintering equipment, the thickness of which is controlled to be 300-350mm, and preheat it to 60-70°C through a heating device;
[0024] S32: Arrange the lower fuel powder layer, spread the fuel powder on the upper part of the lower mixed material layer, control the thickness of the fuel powder to 20 mm to 30 mm, and preheat it to 60 to 70° C. by a heating device;
[0025] S33: Arrange the middle mixed material layer, spread the mixed material balls on the top of the lower fuel powder layer, control the thickness to 300-350mm, and preheat to 60-70℃ by heating equipment;
[0026] S34: Arrange the upper fuel powder layer, spread the fuel powder flatly on the middle mixed material layer, control the thickness of the fuel powder to 20 mm to 30 mm, and preheat it to 60 to 70° C. through a heating device;
[0027] S35: Finally, the upper mixed material layer is arranged, and the mixed material balls are spread flat on the upper fuel powder layer. The thickness is controlled at 300-350 mm, and preheated to 60-70° C. by a heating device.
[0028] Furthermore, the cross-sectional profiles of the lower mixed material layer, lower fuel powder layer, middle mixed material layer, upper fuel powder layer and upper mixed material layer in S3 are set to be isosceles trapezoids that are smaller on the top and larger on the bottom, and the angle between the lower base and the waistline of the isosceles trapezoid is set to 60 degrees; so that the edges and sides of the ultra-thick material layers can also be fully burned, solving the problems of the existing sintering machine trolley edge effect and the poor strength of the surface sintered ore.
[0029] The present invention has the following beneficial effects:
[0030] 1. The present invention adopts multiple mixing treatments during mixing to make the composition of the sintering material uniform, the moisture content appropriate, and easy to make balls. By strengthening the granulation effect of the mixture and improving the particle size composition of the mixture balls, a sintering mixture with good particle size composition is obtained to ensure the sintering quality, increase the output, and improve the air permeability of the sintering material layer.
[0031] 2. When distributing ultra-thick material layers, the present invention adopts a multi-layer distribution method, preheats each layer of material, rationally optimizes the distribution structure, improves the distribution of fuel in the sintering process, enhances the strength of the sintered ore, improves the overall sintering effect, and increases the TFe content of the sintered ore. Under the current raw material structure conditions, while meeting the production needs of the blast furnace, the energy consumption of the sintering process is reduced, and low-carbon and environmentally friendly sintering is achieved.
[0032] 3. The cross-sectional profiles of the lower mixed material layer, lower fuel powder layer, middle mixed material layer, upper fuel powder layer and upper mixed material layer of the present invention are set to be isosceles trapezoids with a small top and a large bottom, so that the edges and sides of the ultra-thick material layers can also be fully burned, solving the problems of the existing sintering machine trolley edge effect and poor strength of the surface sintered ore. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0034] Figure 1 Schematic diagram of the fabric structure of super thick material layer. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0036] See also Figure 1 As shown, the present invention is a low-silicon, low-basicity, vanadium-titanium ultra-thick material layer sintering method, comprising the following steps:
[0037] S1: crushing and sieving the vanadium-titanium concentrate to obtain vanadium-titanium concentrate powder, crushing and sieving the solvent to obtain solvent powder, and crushing and sieving the fuel to obtain fuel powder. The particle size of the vanadium-titanium concentrate powder is controlled to be less than 5 mm, the particle size of the solvent powder is controlled to be less than 3 mm, and the particle size of the fuel powder is controlled to be less than 3 mm. The solvent powder and the fuel powder are dried. After the treatment, the moisture content of the solvent powder is less than 3%, and the moisture content of the fuel powder is less than 10%;
[0038] S2: batching based on mass, and uniformly mixing corresponding weight portions of vanadium-titanium concentrate powder, solvent powder, fuel powder and water, and granulating to obtain mixed material pellets;
[0039] The specific steps include:
[0040] S21: mechanically mix the solvent powder, the fuel powder and 50% by weight of the vanadium-titanium concentrate powder, then add an appropriate amount of water to moisten them, and then mechanically mix them again;
[0041] S22: adding the remaining 25% vanadium titanium concentrate powder to the mixture of S21, and continuing to mix mechanically;
[0042] S23: adding the remaining 25% vanadium titanium concentrate powder to the mixture of S22, and continuing to mix mechanically;
[0043] S24: The mixed material of S23 is processed by a granulation screen to obtain qualified mixed material pellets, and then dried by hot air flow to make the moisture content less than 15%;
[0044] When mixing materials, multiple mixing treatments are adopted, and the vanadium-titanium concentrate powder is added three times, and mechanically mixed multiple times to make the composition of the sintering material uniform, the moisture content appropriate, and easy to make balls. By strengthening the granulation effect of the mixture, the particle size composition of the mixture balls is improved, so as to obtain a sintering mixture with good particle size composition, so as to ensure the sintering quality and increase the output, and improve the permeability of the sintering material layer;
[0045] S3: Arrange an ultra-thick material layer of ≥880mm through a distributor, the ultra-thick material layer includes a lower mixed material layer, a lower fuel powder layer, an intermediate mixed material layer, an upper fuel powder layer and an upper mixed material layer, the cross-sectional profiles of the lower mixed material layer, the lower fuel powder layer, the intermediate mixed material layer, the upper fuel powder layer and the upper mixed material layer are set to be an isosceles trapezoid with a small top and a large bottom, and the angle between the lower base and the waistline of the isosceles trapezoid is set to 60 degrees, and when arranging each layer, preheat the material of each layer;
[0046] The specific steps include:
[0047] S31: first arrange the lower mixed material layer, spread the mixed material balls flat on the sintering equipment, the thickness of which is controlled to be 300-350mm, and preheat it to 60-70°C through a heating device;
[0048] S32: Arrange the lower fuel powder layer, spread the fuel powder on the upper part of the lower mixed material layer, control the thickness of the fuel powder to 20 mm to 30 mm, and preheat it to 60 to 70° C. by a heating device;
[0049] S33: Arrange the middle mixed material layer, spread the mixed material balls on the top of the lower fuel powder layer, control the thickness to 300-350mm, and preheat to 60-70℃ by heating equipment;
[0050] S34: Arrange the upper fuel powder layer, spread the fuel powder flatly on the middle mixed material layer, control the thickness of the fuel powder to 20 mm to 30 mm, and preheat it to 60 to 70° C. through a heating device;
[0051] S35: Finally, the upper mixed material layer is arranged, and the mixed material balls are spread flat on the upper fuel powder layer, and the thickness thereof is controlled to be 300-350 mm, and preheated to 60-70° C. by a heating device;
[0052] When distributing ultra-thick material layers, a multi-layer distribution method is adopted, and each layer of material is preheated to reasonably optimize the distribution structure, improve the distribution of fuel during the sintering process, enhance the strength of the sintered ore, improve the overall sintering effect, and increase the TFe content of the sintered ore. Under the current raw material structure conditions, while meeting the production needs of the blast furnace, the energy consumption of the sintering process is reduced to achieve low-carbon and environmentally friendly sintering;
[0053] S4: start ignition and sintering;
[0054] S5: After sintering is completed, crushed, screened and cooled, a sintered block product is obtained.
[0055] The above are only preferred embodiments of the present invention and do not limit the present invention. Any modification to the technical solutions recorded in the aforementioned embodiments, any equivalent replacement of some of the technical features therein, and any modification, equivalent replacement, and improvement made are all within the protection scope of the present invention.
Claims
1. A method for sintering ultra-thick vanadium-titanium material layers with low silicon content and low basicity, characterized in that: The following steps are involved: S1: crushing and sieving the vanadium-titanium concentrate to obtain vanadium-titanium concentrate powder, crushing and sieving the solvent to obtain solvent powder, crushing and sieving the fuel to obtain fuel powder, and drying the solvent powder and the fuel powder; S2: batching based on mass, and uniformly mixing corresponding weight portions of vanadium-titanium concentrate powder, solvent powder, fuel powder and water, and granulating to obtain mixed material pellets; S3: Arrange the super thick material layer of ≥880mm through the distributor, the super thick material layer includes the lower mixed material layer, the lower fuel powder layer, the middle mixed material layer, the upper fuel powder layer and the upper mixed material layer, and preheat the materials in each layer when arranging each layer; S4: start ignition and sintering; S5: After sintering is completed, crushed, screened and cooled, a sintered block product is obtained; S21: mechanically mix the solvent powder, the fuel powder and 50% by weight of the vanadium-titanium concentrate powder, then add an appropriate amount of water to moisten them, and then mechanically mix them again; S22: adding the remaining 25% vanadium titanium concentrate powder to the mixture of S21, and continuing to mix mechanically; S23: adding the remaining 25% vanadium titanium concentrate powder to the mixture of S22, and continuing to mix mechanically; S24: The mixed material of S23 is processed by a granulation screen to obtain qualified mixed material pellets; S31: first arrange the lower mixed material layer, spread the mixed material balls flat on the sintering equipment, the thickness of which is controlled to be 300-350mm, and preheat it to 60-70°C through a heating device; S32: Arrange the lower fuel powder layer, spread the fuel powder on the upper part of the lower mixed material layer, control the thickness of the fuel powder to 20 mm to 30 mm, and preheat it to 60 to 70° C. by a heating device; S33: Arrange the middle mixed material layer, spread the mixed material balls on the top of the lower fuel powder layer, control the thickness to 300-350mm, and preheat to 60-70℃ by heating equipment; S34: Arrange the upper fuel powder layer, spread the fuel powder flatly on the middle mixed material layer, control the thickness of the fuel powder to 20 mm to 30 mm, and preheat it to 60 to 70° C. through a heating device; S35: Finally, the upper mixed material layer is arranged, and the mixed material balls are spread flat on the upper fuel powder layer. The thickness is controlled at 300-350 mm, and preheated to 60-70° C. by a heating device.
2. A low-silicon, low-basicity, vanadium-titanium ultra-thick material layer sintering method according to claim 1, characterized in that: The particle size of the vanadium-titanium concentrate powder in S1 is controlled to be less than 5 mm, the particle size of the solvent powder is controlled to be less than 3 mm, and the particle size of the fuel powder is controlled to be less than 3 mm.
3. The method for sintering a low-silicon, low-basicity, vanadium-titanium ultra-thick material layer according to claim 1, characterized in that: In S1, after the solvent powder and the fuel powder are dried, the moisture content of the solvent powder is less than 3%, and the moisture content of the fuel powder is less than 10%.
4. A low-silicon, low-basicity, vanadium-titanium ultra-thick material layer sintering method according to claim 1, characterized in that: In S24, the mixed material pellets are dried by hot air flow to make their water content less than 15%.
5. The method for sintering a low-silicon, low-basicity, vanadium-titanium ultra-thick material layer according to claim 1, characterized in that: The cross-sectional profiles of the lower mixed material layer, the lower fuel powder layer, the middle mixed material layer, the upper fuel powder layer and the upper mixed material layer in S3 are set to be isosceles trapezoids with a smaller top and a larger bottom, and the angle between the lower base of the isosceles trapezoid and the waistline is set to 60 degrees.
Citation Information
Patent Citations
Vanadium-titanium concentrate powder thick material layer sintering technology
CN108998660A
Sintering method of high-grade vanadium-titanium-iron ore concentrates
CN112593076A
Cited By
Flexible homogeneous sintering process for super-thick material layer
CN117286333A